2022
DOI: 10.21203/rs.3.rs-1342617/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of sharing experiences on compassion fatigue of family caregivers of the disabled elderly:A Clinical Randomized Trial

Abstract: Background: Caring for the disabled elderly can cause compassion fatigue in family caregivers. Improving social interactions in online social networks can reduce compassion fatigue by increasing social support. The aim of the study was to explore the effect of sharing experiences in an online support group on compassion fatigue of family caregivers of the disabled elderly.Methods: The study conducted as a randomized clinical trial with intervention and control groups. A total of 58 family caregivers of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…To confirm the necessity of implementing the family-centered empowerment model, Jafari et al (20) and Mousavi et al (23) concluded that the family-centered empowerment model's application had a beneficial impact on raising the QoL of chronic patients. Khanjari (16) and Akbari Shakar et al (24) referred to coping skills training setting up a centralized unit for training and support of caregivers as factors affecting their QoL. Besides, A previous study reported that the family-centered intervention has had a positive effect on the elderly's medication management as well as the QoL elderly patients (2), enhancing the process of caring (25).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the necessity of implementing the family-centered empowerment model, Jafari et al (20) and Mousavi et al (23) concluded that the family-centered empowerment model's application had a beneficial impact on raising the QoL of chronic patients. Khanjari (16) and Akbari Shakar et al (24) referred to coping skills training setting up a centralized unit for training and support of caregivers as factors affecting their QoL. Besides, A previous study reported that the family-centered intervention has had a positive effect on the elderly's medication management as well as the QoL elderly patients (2), enhancing the process of caring (25).…”
Section: Discussionmentioning
confidence: 99%